An economical method to measure granular flow in a hopper using a commercial digital camcorder and particle image velocimetry. Issue 3 (3rd May 2016) - Cha, Byoungjun; Park, Junyoung
Abstract: Numerous methods including X-ray imaging, magnetic resonance imaging, and particle image velocimetry (PIV) have been suggested to measure the flow of particles. However, most methods usually require costly equipment. In this study, we measure the velocities of particles in a hopper using a PIV system with open source software and an inexpensive commercial digital camcorder. The proposed system shows high accuracy. The measurement error is less than .5%, and the error of recording speed (frames per second) is about 2.5%. This error rate is negligible because it is lower than the experimental error. Consequently, our findings demonstrate that a PIV system with sufficient accuracy to measure particle flow in a hopper can be developed with a small budget.